2017
DOI: 10.1186/s13104-017-2576-y
|View full text |Cite
|
Sign up to set email alerts
|

A survey of retracted articles in dentistry

Abstract: BackgroundPublication retraction is a mechanism to preserve the scientific literature against publications that contain seriously flawed or erroneous data, redundant publication, plagiarism, unethical research, and other features that compromise the integrity of science. An increase in the occurrence of retractions in recent years has been reported. Nevertheless, there is scarce information on this topic concerning publications in dentistry and related specialties. Thus, this study aimed to investigate retract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 27 publications
3
20
1
3
Order By: Relevance
“…Article retractions arising from research misconduct accounted for 37.5% of retractions, with plagiarism as the most frequently reported reason. The issue of retractions occurring as a result of misconduct is not isolated to the field of obstetrics and gynaecology, with studies in medical oncology, general and plastic surgery, dentistry, orthopaedics, radiology, and neurosurgery demonstrating similar findings . Our results indicated a median H ‐index of 19.0 for the senior author, suggesting that research practices leading to article retraction were not the result of inexperience in publishing …”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Article retractions arising from research misconduct accounted for 37.5% of retractions, with plagiarism as the most frequently reported reason. The issue of retractions occurring as a result of misconduct is not isolated to the field of obstetrics and gynaecology, with studies in medical oncology, general and plastic surgery, dentistry, orthopaedics, radiology, and neurosurgery demonstrating similar findings . Our results indicated a median H ‐index of 19.0 for the senior author, suggesting that research practices leading to article retraction were not the result of inexperience in publishing …”
Section: Discussionsupporting
confidence: 52%
“…The issue of retractions occurring as a result of misconduct is not isolated to the field of obstetrics and gynaecology, with studies in medical oncology, general and plastic surgery, dentistry, orthopaedics, radiology, and neurosurgery demonstrating similar findings. 4,[9][10][11][12][13][14][15][16][17] Our results indicated a median H-index of 19.0 for the senior author, suggesting that research practices leading to article retraction were not the result of inexperience in publishing. 10 Interestingly, retractions were disproportionately higher within gynaecological oncology, accounting for 43% of the withdrawn articles in this study.…”
Section: Discussionmentioning
confidence: 97%
“…The term "honest error/mistake" is frequently used, but it is not clear how journals or publishers establish if an error was honest or purposeful [9]. The reported reasons for retraction are slightly different among medical specialties but misconduct, plagiarism, duplicate publication, or authorship issues are most frequently reported (orthopedics [10], dentistry [11,12], neurosurgery [13], cancer research [14], emergency medicine [15], radiology [16], nursing and midwifery research [17]). Systematic manipulation of the peer review processes by ensuring that a specific article passes the peer review in return for a fee paid by the authors, or for boosting their own publications, and inappropriate authorship, including offering authorship of the article in return for a fee are lately reported [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The method that was used to conduct this research has been utilized in similar research projects (8)(9)(10)(11)(12)(13).…”
Section: Search Strategy and Eligibility Criteriamentioning
confidence: 99%
“…Cokol et al found that, over time, the frequency at which scienti c publications are retracted is increasing (7). Several studies in multiple medical elds have sought to investigate and describe the trends, the global distribution, and the characteristics of these retractions to obtain a deeper understanding of the effect of retractions and the real magnitude of misconduct in medical research (8)(9)(10)(11)(12)(13). For example, Bozzo et al investigated the pattern of oncology publications retraction (8).…”
Section: Introductionmentioning
confidence: 99%